2016
DOI: 10.1186/s12887-016-0748-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent’s subjective perceptions of chronic disease and related psychosocial factors: highlights from an outpatient context study

Abstract: BackgroundAdolescents with chronic disease (CD) can be more vulnerable to adverse psychosocial outcomes. This study aims: 1) to identify differences in psychosocial variables (health-related quality of life, psychosomatic complaints, resilience, self-regulation and social support) among adolescents who feel that CD affects or does not affect school/peers connectedness (measured by self-reported participation in school and social activities); and 2) to assess the extent to which psychosocial variables are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 48 publications
(72 reference statements)
3
28
0
4
Order By: Relevance
“…It has caused the adolescent to be emotionally disturbed and started to default his treatment. Previous studies have shown that excessive rules and high demand for changes in a child and adolescent with a chronic illness will lead to emotional instability and depression (Compas et al 2012;Santos et al 2016). In our case, eventually, we were able to regain back his confidence and self-esteem by engaging well with his opinion and worries.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…It has caused the adolescent to be emotionally disturbed and started to default his treatment. Previous studies have shown that excessive rules and high demand for changes in a child and adolescent with a chronic illness will lead to emotional instability and depression (Compas et al 2012;Santos et al 2016). In our case, eventually, we were able to regain back his confidence and self-esteem by engaging well with his opinion and worries.…”
Section: Resultssupporting
confidence: 49%
“…Furthermore, the sensitivity and specificity of the tests are low, which will not benefit the mass screening in terms of its cost effectiveness. Excessive investigations will also lead to further emotional burden to the child and parents in view of frequent blood takings and imaging procedures that will consume more time, energy and cause more worries (Compas et al 2012;Flynn et al 2017;Rao 2016;Rodriguez-Cruz 2017;Santos et al 2016). Therefore, clinical correlation during the initial assessment is indeed superior in deciding specific investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coincidentally, diets and medications may be troublesome for adolescents if they perceive them as a threat to their independence. As a result, nonadherence to treatment is encountered in a considerable number of adolescent patients . Overprotection by the family may also exacerbate the issues faced by the child.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, nonadherence to treatment is encountered in a considerable number of adolescent patients. [9][10][11] Overprotection by the family may also exacerbate the issues faced by the child. Accordingly, such adjustment problems and psychological factors may contribute to an increased risk of depression in children and adolescents with CF.…”
Section: Introductionmentioning
confidence: 99%